Proverbs and Irony: Their Literary Role in Thomas More's History of Richard III. (June 2014) - Frank, Andrea
Abstract : In his History of King Richard III, Thomas More uses proverbs to demonstrate to the reader how to evaluate characters, events, and ideas in the narrative. Identifying and examining the proverbs reveals subtle irony and wisdom. For example, when Richard chooses "a sure foundation" for his plans, a proverb is the starting point from which the reader evaluates Richard's actions, compares them to Edward's, and raises perennial questions of how to govern rightly. Similarly, proverbs in the queen's argument for keeping her son show the error of her decision. Finally, the bishop of Ely's proverbs and fable demonstrate the power and danger of words in the government and highlight qualities of a good leader which are otherwise lacking in the History .